Bad Shakespeare: Performing Failure - Anna Blackwell (Humanities)
The Shakespearean actor is a readily recognisable figure within the transatlantic cultural landscape. They may move regularly between the theatrical environs, which garnered them the appellation and more mainstream fare in television or film, but they are always, somehow, Shakespearean. However, if easily identified, the Shakespearean actor is harder to define. For example, the multi-volume Great Shakespeareans shortlists individuals who, in editors Peter Holland’s and Adrian Poole’s words, have had ‘the greatest influence on both the interpretation, understanding and reception of Shakespeare, both nationally and internationally’). But such scholarly endeavours consistently stop short of describing any social or cultural function which the Shakespearean may fill or any implicit ideological work at hand in the naming of actors as Shakespeareans. These omissions are all the more curious because, while its attribution is inherently positive in the examples above, popular culture also abounds with rather less illustrious Shakespeareans. Consider, for instance, how Niles and Frasier Crane watched, appalled, while their childhood icon, Jackson Hedley (Derek Jacobi), gurned and groaned on stage. Playing a caricature of himself in Extras, meanwhile, Ian McKellen confides that he knew what to say in The Lord of the Rings because ‘the words were written down for me’. Welcome to bad Shakespeare: a trope that has existed for as long as there has been the potential for ‘good’ Shakespeareanism. For evidence, one needs only consider Hamlet’s stubborn insistence that actors deliver their lines ‘trippingly on the tongue’. Bad Shakespeare has no such luck, however. From Mr Wopsle in Great Expectations to Alan Rickman’s frustrated thespian-turned-science-fiction-star in Galaxy Quest (‘How did I come to this? I played Richard III. There were five curtain calls’), these Shakespeareans are hammy, self-congratulating and embarrassing; they exhibit what David McGowan calls ‘visible acting’. Reversing a more typical focus on prestige and skill, this article will reflect on what it says about our relationship to Shakespeare that we take such evident and knowing pleasure in watching highly respected performers apparently fail at their jobs. Building on film studies and scholarship on badfilms, I will consider whether these fictional performances of failure only reify existing norms of ‘good’ performance or if they offer more subversive possibilities.